THE INFLUENCE OF THE MATERIAL TYPE ON THE RESERVOIR AIR PRESSURE IN THE KNIFE TOOL HEATING FURNACE - Wijaya, Ikhlasul Amal; Hermawan, Rudi; Firizal, Harlin; Ramadhan, Anugrah Agung (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
A reservoir is a vessel or storage container used to store pressure resulting from the evaporation of a liquid. In its use, the Reservoir's constituent material must be good to produce maximum results. This experimental research aims to study the influence of the reservoir material types, such as aluminum, steel, and stainless steel, on the air pressure produced by each material[R1] . The experiment was conducted by aluminium, steel, and stainless steel material testing. The results showed that aluminum, steel, and stainless steel produce a pressure of 2.00 bar, 2.50 bar, 1.50 bar, respectively.. The comparison of results shows that the type of reservoir material will affect the final result of reservoir pressure.